1995
DOI: 10.1093/aesa/88.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Scale Morphology Effects on Feeding Behavior and Biological Control Potential of Rhyzobius lophanthae (Coleoptera: Coccinellidae)

Abstract: We compared the morphological characteristics of the scale covers and bodies of 2 economically important scale species, California red scale, Aonidiella aurantii (Maskell), and oleander scale, Aspidiotus nerii (Bouche), to determine their protective value against predation by the coccinellid Rhyzobius lophanthae (Blaisdell). We also compared the morphology of the mandibles of R. lophanthae with that of Chilocorus cacti (L.), a specific predator of diaspidid scales. A higher percentage of R. lophanthae larvae s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…The consumption of the different phenological stages of S. oleae depends mostly on the characteristics of the tegument of the prey [5], the relation between the sizes of predator and prey and also the nutritional quality of the prey [11]. Easily penetrated covers are more likely to be suppressed than thick covers [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption of the different phenological stages of S. oleae depends mostly on the characteristics of the tegument of the prey [5], the relation between the sizes of predator and prey and also the nutritional quality of the prey [11]. Easily penetrated covers are more likely to be suppressed than thick covers [5].…”
Section: Resultsmentioning
confidence: 99%
“…Easily penetrated covers are more likely to be suppressed than thick covers [5]. In this way, it was probable that first instar nymphs are softer and easier to handle by smaller coccinellid species (e. g. S. mediterraneus) than the second instar nymphs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the development of R. lo phanthae on scales with harder scale cover [like Aonidiella aurantii (Maskell) and Chrysomphalus aonidum (Linnaeus)] is more difficult than on scales with softer scale cover (like Aspidiotus nerii Bouche) (Stathas 2000b, 2001b, Stathas et al 2002. Honda and Luck (1995) attribute the incapability of rearing R. lophanthe on diaspidids with hard scale cover to the morphological characteristics of its moufhparts. Bruwer and Schoeman (1988) reared L. gloverii in laboratory on several preys and tem peratures, and found that the mean optimum fecundity was 44.2 crawlers/female, in sour orange trees at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the cover might provide protection against predators (Foldi 1983;Gullan and Kosztarab 1997). However, this mechanism has not been so clearly described as in other scale insects with harder covers, such as soft (Hemiptera: Coccidae) and armored scales (Hemiptera: Diaspididae) (Daane et al 2000;Gullan and Kosztarab 1997;Honda and Luck 1995;Tena and Garcia-Marí 2008). On the other hand, the absence of a sclerotized cover allows mealybugs to carry out evasive movements similar to those performed by aphids (Hemiptera: Aphididae) (De Farias and Hopper 1999;Wyckhuys et al 2008).…”
Section: Introductionmentioning
confidence: 99%